Work ability of informal caregivers of patients treated by the public home care service of Brazil: A cross-sectional study - Gregio Neto, Nelson [UNESP]; Spröesser Alonso, Melissa [UNESP]; Bernardes, João Marcos [UNESP]; Ruiz-Frutos, Carlos; Gómez-Salgado, Juan; Dias, Adriano [UNESP] (Elsevier, 2021)
Informal caregivers are subject to a heavy work burden, which can have negative repercussions on their work ability. This cross-sectional study with 70 informal caregivers aims to evaluate the work ability of informal caregivers caring at home for patients followed by the Public Home Care Service in Bauru, Brazil, as well as to investigate its associated factors. The association between work ability and the variables under study was estimated using simple and multiple logistic regression models, including a hierarchical model. Work ability, care-related burden, sleep quality and quality of life were assessed through the Work Ability Index, the Zarit Burden Interview Scale, the Mini-sleep Questionnaire, and the 12-Item Short-Form Health Survey, respectively. Almost 36% of the informal caregivers had an inadequate work ability. The variables that increased the probability of an adequate work ability were quality of life (OR: 0.94; CI: 0.92–0.97) and self-perceived physical fitness (OR: 0.32; CI: 0.17–0.60), while those that reduced the likelihood of adequate work ability were age (OR: 1.06; CI: 1.02–1.13), burden (OR: 1.05; CI: 1.01–1.10) and poor sleep quality (OR: 1.07; CI: 1.01–1.12). It is necessary to develop public health policies aimed at informal caregivers who, due to their informality, are not seen as workers.
Keywords: Caregivers; Cross-sectional study; Home Care Services; Occupational Health; Quality of life; Work capacity evaluation